Integrating Kyai’s Authority into Sharia Mediation: A Socio-Legal Approach to Legal Pluralism and Family Law Harmony in Madura - Mohsi Mohsi; Muchlis Muchlis; Fahmi Assulthoni (Mafapress - Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA Pati, 2026)
This study investigates the pivotal role of the Kyai in Sharia mediation and the integration of their religious authority with the Indonesian national legal system within family law disputes in Madura. Utilizing a qualitative socio-legal approach, the research explores the dynamics of legal pluralism and the harmonization between Sharia and state law. The findings reveal that while the Madurese community predominantly favors Sharia mediation led by Kyais due to high social trust, these religious figures do not operate in isolation from formal law. Instead, Kyais actively bridge the gap by considering state legal frameworks, particularly in protecting women’s rights during divorce and inheritance disputes. This study proposes the concept of